Pelatihan Pendekatan Humanistik Dalam Pembelajaran Bahasa Inggris Bagi Mahasiswa Pendidikan Bahasa Inggris - Zuhriyah, Mukminatus; Muthmainnah, Nur; Daristin, Pipit Ertika (Fakultas Tarbiyah IAIN Kediri, 2024)
Conventional English learning models often emphasize learning on explicit English grammar mastery and the learning process is dominated by the teacher. This happens to English language education students carrying out teaching practice at schools so that the target of learning English at the schools is not achieved optimally. Therefore, the PkM team, which is a collaborative team from Universitas Hasyim Asy'ari Tebuireng Jombang and UIN Salatiga, agreed that students who will carry out teaching practice in schools need to be given training on a humanistic approach in learning English. Participants in this online training were 53 English language education students from two private universities in East Java and one state university in Central Java. This training was carried out for a week online, consisting of material presentations and assistance in making lesson plans based on a humanistic approach. After attending this training, students are increasingly able to understand how to teach in English classes. Students' understanding of the humanistic approach has increased and their lesson plans have also implemented a humanistic approach. In general, this training really needs to be provided as a provision for English language education students in carrying out teaching practices at schools.